2013
DOI: 10.1016/j.bbadis.2013.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Spinal muscular atrophy: An update on therapeutic progress

Abstract: Humans have two nearly identical copies of survival motor neuron gene: SMN1 and SMN2. Deletion or mutation of SMN1 combined with the inability of SMN2 to compensate for the loss of SMN1 results in spinal muscular atrophy (SMA), a leading genetic cause of infant mortality. SMA affects 1 in ~6000 live births, a frequency much higher than in several genetic diseases. The major known defect of SMN2 is the predominant exon 7 skipping that leads to production of a truncated protein (SMNΔ7), which is unstable. Theref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 156 publications
(170 reference statements)
1
47
1
1
Order By: Relevance
“…In weight-matched litters (2.99 ± 0.24 g versus 2.94 ± 0.26 g), the ML372-treated cohort displayed substantially greater weight gain compared with vehicle-treated controls (maximal weight of 5.63 g versus 3.87 g) ( Figure 5A). Weight gain in compound-treated littermates has previously been shown to correlate with the potential efficacy of a compound under therapeutic consideration for SMA (11). Moreover, the onset of weight loss was delayed in ML372-treated animals.…”
Section: Ml372 Is Brain Penetrant and Has A Reasonable Exposure And Hmentioning
confidence: 83%
See 1 more Smart Citation
“…In weight-matched litters (2.99 ± 0.24 g versus 2.94 ± 0.26 g), the ML372-treated cohort displayed substantially greater weight gain compared with vehicle-treated controls (maximal weight of 5.63 g versus 3.87 g) ( Figure 5A). Weight gain in compound-treated littermates has previously been shown to correlate with the potential efficacy of a compound under therapeutic consideration for SMA (11). Moreover, the onset of weight loss was delayed in ML372-treated animals.…”
Section: Ml372 Is Brain Penetrant and Has A Reasonable Exposure And Hmentioning
confidence: 83%
“…SMA is the consequence of loss of the SMN1 gene, with the number of copies of SMN2 acting as a disease modifier (6,(8)(9)(10). Current investigational approaches to enhance SMN protein levels include increasing SMN2 exon 7 inclusion, increasing overall SMN2 transcript expression, and stabilizing the residual SMN protein in SMA patients (11,12). While the mechanisms that regulate SMN2 splicing have been well documented, less is known about the factors that govern SMN protein stability.…”
Section: Introductionmentioning
confidence: 99%
“…The neuroprotective properties of drug have been established in numerous forms of severe central nervous system damages, such as stroke, traumatic brain injury and spinal cord injury. The drug preserves the brain from impairment development via anti-inflammatory, antiapoptotic and neurotrophic effects [19][20][21][22]. Elderly are usually more at risk to the adverse effects of VPA than younger adults.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding clinical trials, ISIS Pharmaceuticals has recently concluded a phase 1 trial in which the safety, tolerability, and pharmacokinetics of escalating doses of the ISIS-SMNRx drug, an ISS-N1-targeting MOE SSO, administered into the spinal fluid as a single injection in patients with SMA (NCT01494701) has been evaluated (Southwell et al, 2012). Moreover, a phase 2 clinical trial has been initiated in patients with infantile-onset spinal muscular atrophy (NCT01839656) (Seo et al, 2013).…”
Section: Cns As Target For Antisense Therapymentioning
confidence: 99%
“…In general, a variety of cis-acting RNA sequences of the SMN2 gene have been targeted by different oligonucleotide chemistries, such as 2¢-OMe, 2¢-O-MOE or morpholino. In particular, the discovery of the intronic splicing silencer N1 (ISS-N1) was an important breakthrough and many reports selected this sequence as the target for SSO treatment (Seo et al, 2013). As previous steps to apply SSO therapy to cure SMA in humans, intrathecal infusion of the SSO was assayed in cynomolgus monkeys, showing this strategy provided therapeutic levels of SSO to all regions of the spinal cord (Passini et al, 2011).…”
Section: Cns As Target For Antisense Therapymentioning
confidence: 99%